Software Visualization of Porous Media with Emphasis on Mass Flow Rate Determinaton as Temperature Changes - Mukaila, Olagunju; Sadik, J.S (Journal of Asian Scientific Research, 2012)
Background: Software development has been in existence since the last three decades, when the computer age started, as the software developments became more complex, so does the task of understanding them. Even some time, it is very difficult for the developers to interpret the source and object codes to the users. Objective: Based on the problems mentioned above, this work is developed software visualization for porous media with Graphical User Interface (GUI) application. Software visualization (SV) uses computer graphics to communicate the structure and behavior of computer software and algorithms. Fluid, which comprise both liquid and gases play very vital roles in human life and machines performances. This fluid always becomes useful when it tranfers or move from one point to another and this normally possible through pipe. The quantity or mass of fluid that passes through the pipe need to be determined especialy by the designers of pipe and the end users of the fluid. Method: Inorder to develop the software visualization for this work, the model which based on modified Heagen equation was modified to determine different mass flow rate at different temperature. The visual pipe for representation of different mass flow rate was developed with Autodesk Mayer and embedded in C# program for easy visualization. Results: With this software visualization, easy visualization of mass flow partterns can be examined and viewed. Conclution: This work will definitely assist the experts in fluid, pipes designers, and end users of fluid to determine at ease and at safe cost series of mass flow rate at different temperature.